PENGARUH TATA RUANG KANTOR TERHADAP EFEKTIVITAS ORGANISASI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SUMEDANG - Edi Setiawan; Dina Handayani; M. Rizal Fadilah; Nur Azizah; Rifki Firdaus; Sari Rahmadini (Journal Of Regional Public Administration (JRPA), 2020)
This study aims to determine the Office Layout and Organizational Effectiveness, to determine the relationship between Office Layout and Organizational Effectiveness and to determine the magnitude of the influence of Office Layout on Organizational Effectiveness at the Office of the Ministry of Religion, Sumedang Regency. This research uses descriptive analysis method with a quantitative approach and the type of statistics used is descriptive statistics saturated sampling technique. As for the population in this study were 69 employees of the Ministry of Religious Affairs in Sumedang Regency. The analysis used includes the calculation of the percentage, normality test, correlation test, significance test and determination coefficient test. Based on the research results it is known that the Office Layout at the Ministry of Religion Office of Sumedang Regency is 71.99%. Furthermore, the results of research on Organizational Effectiveness at the Ministry of Religion Office of Sumedang Regency amounted to 76.77%. The relationship between Office Spatial Planning and Organizational Effectiveness at the Office of the Ministry of Religious Affairs in Sumedang Regency is at a strong correlation level with a correlation coefficient of 0.764. Based on the significance test it is stated that there is a positive and significant relationship between Office Layout and Organizational Effectiveness at the Office of the Ministry of Religion, Sumedang Regency. As well as the influence of Office Layout on Organizational Effectiveness reaching 58.4% in the medium category. The remaining 41.6% is influenced by other factors not taken into account in the study. Based on the results of this study, the Office of the Ministry of Religion of Sumedang Regency should pay more attention to the design or arrangement of office space, because with good office space arrangement it will provide work comfort and satisfaction for employees in order to increase organizational effectiveness.